دراسة كمية تحليلية لإنتاج القطاع الزراعي بمطاحن بشار خلال الفترة - محوز ،خضرة; بن عامر، مصطفى (جامعة الوادي University of Eloued, 2024)
إن الاستخدام الأمثل للموارد البشرية والمادية يؤدي الى زيادة الإنتاج والإنتاجية والكفاءة، وهذا يتطلب التخلي عن الأساليب القديمة التي لم تعد تتلاءم مع التحديات التي تواجهها المؤسسات والواقع الاقتصادي، وتبني تقنيات الإنتاج الحديثة والفعالة، وهذا ما أدى الى نمو وتطور بعض الطرق الكمية والإحصائية، وخاصة تقنيات البحث التشغيلي في الادارة، والتي تمثل تقدما أساسيا في صنع القرار. البحث التشغيلي هو أداة تساعد الادارة في ترشيد عملية صنع القرار وهي فعالة في المساعدة الاختيار بين عدة بدائل ممكنة ضمن الخطة الاستراتيجية للمؤسسة، وتكمن أهمية هذا الموضوع في ابراز ضرورة استخدام تقنيات الإدارة العملية الحديثة وكشف النقائص في هذا الصدد بمؤسسة مطاحن بشار، خاصة في ظل ظروفها الاقتصادية. وهذا ما دفعنا إلى البحث عن حلول عملية لهذه المشكلة لتقييم حالة انتاجها خلال الفترة (2019-2021). The optimal use of human and material resources leads to increased production, productivity, and efficiency. This requires abandoning outdated methods that no longer align with the challenges faced by institutions and the economic reality, and instead adopting modern, efficient production techniques. This has led to the growth and development of some quantitative and statistical methods, especially operational research techniques in management, which represent a fundamental advancement in decision-making science. Operational research is a tool that aids management in rationalizing the decision-making process and is effective in helping choose between several possible alternatives within the institution's strategic plan. The importance of this topic lies in highlighting the necessity of using modern scientific management techniques and revealing the shortcomings in this regard at the Béchar Mills institution, particularly in light of its economic conditions. This prompted us to assess its production status during the period (2019-2021
مقال
Keywords: استخدام أمثل; انتاج وانتاجية; اتخاذ القرار; مطاحن بشار: Optimal use; Production and productivity; Linear programming; Decision-making; Béchar Mil